2019
DOI: 10.1177/1474515119885240
|View full text |Cite
|
Sign up to set email alerts
|

Acceptance of illness mediate the effects of health literacy on self-management behaviour

Abstract: Background: Self-management is crucial for blood pressure control and subsequent disease prevention. Health literacy and acceptance of illness may contribute to self-management behaviour; in addition, acceptance of illness may mediate the effects of health literacy on self-management behaviour among patients with hypertension. Objective: The aims of the research were to examine whether health literacy and acceptance of illness were associated with both pharmacological and non-pharmacological management behavio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 25 publications
3
19
0
1
Order By: Relevance
“…When patients with chronic diseases accept the disease, pain, depression, and anxiety decrease, and physical well-being and quality of life improve [41]. Moreover, self-management behavior increases [42]. These are all consistent with the current results.…”
Section: Discussionsupporting
confidence: 90%
“…When patients with chronic diseases accept the disease, pain, depression, and anxiety decrease, and physical well-being and quality of life improve [41]. Moreover, self-management behavior increases [42]. These are all consistent with the current results.…”
Section: Discussionsupporting
confidence: 90%
“…We are able to extend this finding by adding psychological measures that show distinct differences in self-efficacy, motivation and illness perceptions between clusters when patients are grouped solely on health literacy responses. This shows promise as an effective avenue for self-management interventions, as acceptance of the condition has previously been shown to mediate health literacy in self-management of hypertension [43].…”
Section: Discussionmentioning
confidence: 97%
“…In our observation, men with high illness acceptance were much more likely to declare that they complied with medical advice and take their prescribed medications regularly. A study by Chinese authors similarly showed a positive correlation between illness acceptance and pro-health behaviour in terms of the non-pharmacological and pharmacological management of arterial hypertension [20].…”
Section: Discussionmentioning
confidence: 91%